RUANG GENDER PADA RUMAH TINGGAL: KAJIAN TRANSFORMASI BUDAYA DALAM KEBUDAYAAN JAWA - Martino Dwi Nugroho (Ars: Jurnal Seni Rupa dan Desain, 2008)
hi general discourse, it is nut possible to discuss "gender" without bringing out the man-womanrelation features. The enthusiasm on the discussion increases, following the people awareness concerning togender relation and position. Javanese culture maintains a unique family interrelation system. Inside thisarrangement, we can explore the position and role o f a person inside the community as well as the man andwoman interrelation.This research describes the system as the gender relation. The Javanese is a patriarchy community,xoho sets certain gender-related boundaries to show man domination over woman within the society.From the historical background, the gender relation inside Javanese community roas represented on thearchitectural spacc. The rcscarch reveals the layout concept o f traditional Javanese house from previousera, whereas the space concept is still initiated by the gender boundary. Architecture as the product ofhuman culture implements the community socio-cultural condition and psychology. The same situationalso occurred on the gender separation from the social environment and community psychology. In presenttime, the modernization, woman emancipation and the penetration o f western culture are the basis forthe transformation o f gender position and relation to be occurred inside the Javanese community. Thetransformation itself is pointed out to equal man and woman status and position more. The transformationpattern o f gender relation, especially occurred within the Javanese family, slowly shifted the gender conceptinside the house. The transformation o f the gender concept could be generalized and derived into significantpatterns o f room function and organization transformation, the intention o f space and also the orientation.Jit this era, the transformation also alters the pattern o f room layout to a more neutral space.Keywords: gender, interior, transformation, Javanese culture